Bronsted Acid Catalyzed Morita-Baylis-Hillman Reaction: A New Mechanistic View for Thioureas Revealed by ESI-MS(/MS) Monitoring and DFT Calculations - Amarante, Giovanni W.; Benassi, Mario; Milagre, Humberto M. S. [UNESP]; Braga, Ataualpa A. C.; Maseras, Feliu; Eberlin, Marcos N.; Coelho, Fernando (Wiley-v C H Verlag Gmbh, 2009)
A Morita-Baylis-Hillman (MBH) reaction catalyzed by thiourea was monitored by ESI-MS(/MS) and key intermediates were intercepted and characterized. These intermediates Suggest that thiourea acts as an organocatalyst in all steps of the MBH reaction cycle, including the rate-limiting proton-transfer step. DFT calculations, performed for a model MBH reaction between formaldehyde and acrolein with trimethylamine as base and in the presence or the absence of thiourea, suggest that thiourea accelerates MBH reactions by decreasing the transition-state (TS) energies through bidentate hydrogen bonding throughout the whole catalytic cycle. In the rate-limiting proton-transfer step, the thiourea acts not as a proton shuttle, but as a Bronsted acid stabilizing the basic oxygen center that is formed in the TS.
Keywords: Density functional calculations; ESI mass spectrometry; Morita-Baylis-Hillman reaction; reaction mechanisms; thiourea